Consequences of the Formation of Government Regulation Number 60 of 2016 concerning Bnp Not Fulfilling the Rules of Establishing Prevailing Laws - Aryanto Sofyan (Fakultas Hukum Universitas Lampung, 2020)
The formation of laws and regulations must be based on the norms that underlie their formation. Government regulations are derivative rules for implementing laws. In the draft Government Regulation, the Ministry has the authority to propose a draft to the President. This study aims to determine whether Government Regulation no. 60 of 2016 concerning Types and Rates of Types of Non-Tax State Revenue (PNBP) has met the principles of forming good laws and regulations and knows the legal consequences that occur if these regulations do not meet the rules for forming good laws and regulations. This type of research is normative juridical legal research. Normatively doing research by assessing the sources of law related to the issues raised. The results of the study show that Government Regulation Number 60 of 2016 concerning Types and Rates of Non-Tax State Revenue (PNBP) does not meet the rules of forming good laws and regulations.